Report on industrial attachment with Singapore Institute of Manufacturing Technology - Parthasarathi Rishikesh. (2008)
This report describes Building an infrared sensor module and integrating it with a Sonar Module. Principle of Infrared obstacle detection and distance calculation is explained with various experiments and setup.